A Switch to Polyunsaturated Fatty Acid Based Ketogenic Diet Improves Seizure Control in Patients with Drug-resistant Epilepsy on the Mixed Fat Ketogenic Diet: A Retrospective Open Label Trial - Nathan, Janak (Cureus, 2019)
Introduction The ketogenic diet (KD) is used for drug-resistant epilepsy. However, some patients find only a modest benefit, which may plateau over time. Evidence from several animal and human studies suggests that polyunsaturated fatty acids (PUFAs) may be a beneficial form of treatment for these patients. This retrospective study was conducted to evaluate whether a switch from classic mixed fats KD (MFKD) to a natural polyunsaturated fatty acid KD (PUFA-KD) would improve seizure control. Methods The study evaluated the medical paper record forms of patients who had at least one seizure per week despite the use of MFKD. These patients were started on PUFA-KD and grouped according to the oils preferred. We analyzed the effect on seizure control, tolerability, blood lipids, and adverse effects and whether the type of seizures, age of seizure onset, age at which KD was started, and the ratio of omega 6: omega 3 (n6:n3) fatty acids had any effect on seizure control. Results Data from fifty patients (aged 10 months to 35 years) were analyzed. At the end of six and 12 months on the PUFA-KD, 12% (6) and 16% (8) were seizure-free and 82% (41) and 88% (44) had a >50% reduction in seizures, respectively. The mean seizure control at 12 months was highest in patients with mixed seizures followed by those with generalized seizures and lowest for those with focal seizures. Seizure control at 12 months was inversely correlated to the age of onset of epilepsy and age at initiation of KD. This improvement was independent of the type of PUFAs and the ratio of n6:n3 used. The PUFA-KD was generally well tolerated. Blood lipid levels significantly improved. Conclusion Changing to PUFA-KD improved seizure control in patients who did not respond satisfactorily to MFKD.